Renal handling of amphotericin B and amphotericin B-deoxycholate and potential renal drug-drug interactions with selected antivirals - Trejtnar, František; Mandíková, Jana; Kočíncová, Jana; Volková, Marie (Antimicrobial agents and chemotherapy, 2014)
Amphotericin B (AmB) is excreted via the renal excretion route. This excretion process may result in nephrotoxicity. However, relevant information on the precise renal excretion mechanisms is not available. The aim of the study was to analyze the possible interaction of AmB or its prodrug AmB deoxycholate (AmB-DOC) with the typical renal organic anion transporters (OATs) and organic cation transporters (OCTs), using cellular and organ models. The relevant transport systems were then investigated in terms of the drug-drug interactions of AmB-DOC with antivirals that might potentially be used concomitantly. To analyze the renal excretion mechanisms of [(3)H]AmB, perfused rat kidney was employed. HeLa and MDCK II cells transiently transfected with human OAT1 (hOAT1) or hOCT2 were used as the cellular models. A significant tubular secretion of AmB was demonstrated in the perfused rat kidney. The cellular studies performed confirmed the active transport of AmB into cells. AmB did not interact with hOAT1 but strongly inhibited hOCT2. In contrast, AmB-DOC inhibited both hOAT1 and hOCT2. However, [(3)H]AmB cellular uptake by hOAT1 and hOCT2 was not found. AmB-DOC interacted significantly with adefovir, tenofovir, and cidofovir in hOAT1-transfected cells at supratherapeutic concentrations. In conclusion, the significant potency of AmB and AmB-DOC for inhibiting the transporters was demonstrated in this study. The secretion of AmB in the renal tubules is likely not related to the transporters here, since the drug was not proven to be a substrate for them. Drug-drug interactions of AmB and the antivirals used in this study on the investigated transporters are not probable.
Keywords: Drug Interactions; Cell Line; Rats; psi; lidé; kyselina deoxycholová; Dogs; HeLa Cells; proteiny přenášející organické kationty; Rats, Wistar; mužské pohlaví; Organic Cation Transport Proteins; antivirové látky; Drug Combinations; fixní kombinace léků; krysa rodu Rattus; Organic Anion Transport Protein 1; protein 1 přenášející organické anionty; amfotericin B; zvířata; Humans; Temperature; Amphotericin B; ledviny; lékové interakce; buněčné linie; Deoxycholic Acid; potkani Wistar; Kidney; Antiviral Agents; HeLa buňky; teplota; Male; Animals